Environmental Monitoring Research 2000–2026 Growth Themes and Collaboration Patterns: A Bibliometric Investigation - Judijanto, Loso (West Science Nature and Technology, 2026)
This study investigates the evolution, thematic structure, and collaboration patterns of environmental monitoring research from 2000 to 2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, and collaboration networks among authors and countries. The results indicate a significant increase in research output, particularly after 2015, reflecting growing global concern over environmental degradation, climate change, and sustainability issues. The keyword co-occurrence analysis reveals several dominant research clusters, including pollution and chemical analysis, human health and air quality, ecological and biodiversity studies, and technology-driven monitoring approaches. Emerging themes such as artificial intelligence, machine learning, and remote sensing highlight a shift toward digital and data-intensive environmental monitoring systems. The density analysis further confirms that while traditional topics such as pollution and chemistry remain central, newer themes related to smart monitoring and sustainability are gaining momentum. In terms of collaboration, developed countries continue to dominate global research networks, although participation from developing regions is increasing. This study contributes to the literature by providing a comprehensive overview of the intellectual development of environmental monitoring research and identifying future directions that emphasize technological innovation, interdisciplinary integration, and global collaboration.